PENGARUH PENYAJIAN LAPORAN PERTANGGUNGJAWABAN, AKSESIBILITAS, DAN KOMITMEN ORGANISASI PEMERINTAH DESA TERHADAP AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA - Intan Cristuin Monica; Herdianto Herdianto; Furqonti Ranidiah; Rina Yuniarti (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This research aims to determine the influence of the presentation of accountability reports and the commitment of village government organizations on the accountability of managing village fund allocations. The results of this research show that the presentation of the t test accountability report has a significance level of 0.004, which means <0.05. This shows that this research supports the first hypothesis (H1 is accepted). The t-test Accessibility variable has a significance level of 0.621, which means >0.05. This shows that this research does not support the first hypothesis (H2 is not accepted). The organizational commitment variable in the t test has a significance level of 0.000, which means <0.05. This shows that this research supports the third hypothesis (H3 is accepted). Furthermore, together the presentation of accountability reports, accessibility and organizational commitment influence the accountability of Village Fund Allocation which can be seen in the F test results which have a significance value of 0.000 which means <0.05. This shows that this research supports the third hypothesis (H4 is accepted). Thus, H1 is accepted, which means that the presentation of accountability reports affects the accountability of village fund management, H2 is rejected, which means that accessibility has no effect on the accountability of village fund management, H3 is accepted, which means that organizational commitment has an effect on the accountability of village fund management. H4 is accepted, which means that together the presentation of accountability reports, accessibility and organizational commitment influence the accountability of village fund allocation.  Keywords: Accountability Report, Accessibility, Organizational Commitment, Accountability of Village Fund Allocation